2011
DOI: 10.1007/s10658-011-9747-9
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of fungi (Fusarium and Rhizoctonia) and oomycetes (Phytophthora and Pythium) associated with apple orchards in South Africa

Abstract: Several species of fungi and oomycetes including Fusarium, Rhizoctonia,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
84
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 121 publications
(88 citation statements)
references
References 40 publications
4
84
0
Order By: Relevance
“…For instance, P. vexans, which has the ability to infect coarser host tissues such as stems and trunks (Van der Plaats-Niterink 1981; Zeng et al 2005; this study) could be easily detected from root systems, while P. irregulare, which is usually associated with fine, brittle rootlets that tend to disintegrate (Bumbieris 1972), was only detected at low levels. This general lack of correlation between the amount of pathogen DNA concentration in roots, and plant growth inhibition has also been reported for oomycete pathogens on apple (Tewoldemedhin et al 2011). The low levels of DNA detected for Ph.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…For instance, P. vexans, which has the ability to infect coarser host tissues such as stems and trunks (Van der Plaats-Niterink 1981; Zeng et al 2005; this study) could be easily detected from root systems, while P. irregulare, which is usually associated with fine, brittle rootlets that tend to disintegrate (Bumbieris 1972), was only detected at low levels. This general lack of correlation between the amount of pathogen DNA concentration in roots, and plant growth inhibition has also been reported for oomycete pathogens on apple (Tewoldemedhin et al 2011). The low levels of DNA detected for Ph.…”
Section: Discussionmentioning
confidence: 53%
“…On tree crops, P. vexans causes root rot and necrosis on durian (Durio zibethinus L.; Vawdrey et al 2005), macadamia (Macadamia integrifolia Maiden and Betche; Serfontein et al 2008) and apple trees (Malus spp. ; Tewoldemedhin et al 2011), seedling damping-off of wild cashew (Anacardium excelsum L.; Davidson et al 2000), cankers on trunks of rubber trees (Hevea brasiliensis Müller Argoviensis; Zeng et al 2005) and lesions on trunks of Eucalyptus spp. (Linde et al 1994).…”
Section: Discussionmentioning
confidence: 99%
“…3; Table 3). These species were recovered with low frequency from roots in the previous study and traces were reported in literature on apple (Kelderer et al, 2012;Manici et al, 2013;Mazzola, 1998;Tewoldemedhin et al, 2011). This indicates that F. avenaceum and F. venenatum are soil inhabiting species typical in European apple orchards, but they do not commonly colonize roots; therefore, their presence everywhere in native soils suggests further investigation on negative impact on plants growth that may be due to phytotoxic metabolites released in rhizosphere, as they are one component of Fusarium spp.…”
Section: Fungal Communitiesmentioning
confidence: 60%
“…These ubiquitous Fusarium spp. were largely reported as the most active genus in colonizing plant roots (Hancock, 1985;Maciá-Vicente et al, 2008;Manici and Caputo, 2010), with prevalent nonpathogenic interaction with woody plants as reported in previous studies in which their interaction with apple plant was assessed (Manici et al, 2003;Tewoldemedhin et al, 2011).…”
Section: Fungal Communitiesmentioning
confidence: 83%
See 1 more Smart Citation